QARAQALPAQ XALÍQ DÁSTÚR QOSÍQLARÍ – XALQÍMÍZDÍŃ ÁJAYIP ÓNERLERINIŃ BIRI - Xodjametova, G. (SCIENCE and SOCIETY, 2022)
The people of Karakalpakstan have a rich cultural heritage. In particular, oral literature has been an integral part of our people for centuries, reflecting dreams, despair, important events that left a deep mark in our national history.